Religion in its Diaspora - Kahlia Brown (Caribbean Studies Students' Union, 2022)
Through the forced migration of various peoples by colonial powers, the Caribbean has become a melting pot of a wide array of races, cultures, and religions. However, the existence of Hinduism in the Caribbean is often unknown to those outside of the Caribbean and its diaspora, and is sometimes overlooked within the region. Much like other social, cultural and religious artefacts in the region, Hinduism in the Caribbean has became distinct from its origins, through a unique process of 'creolization'. This essay seeks to contextualize Hinduism in the Caribbean from the 19th century onward, considering factors that have led to the evolution of Caribbean Hinduism in Guyana and Trinidad & Tobago, while acknowledg- ing the dangers of using this evolution to define the religion as a whole.